First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations Members of the Medical and Lay Councils of the League laid before the meeting the aims and objects of the League, when the support of the Lord Mayors and Mayors present was invited in establishing Branches of the League in the principal cities of the country. On December 15th a public meeting was held at the City Hall, Cardiff, convened by the Lord Mayor, when members of the Medical Council of the League spoke on the need of raising the standard of health of the nation, and the aims and objects of the League were laid before the meeting. The following resolution was put to the meeting from the chair: "That the People's League of Health is in every way worthy of support, that a Branch of the League shall be established in Cardiff, and that a Committee shall be formed as a result of the meeting." The resolution was seconded by Professor Edgar Collis and was carried unanimously. At a meeting of this Committee the following day a committee was formed, at which the following were elected to the Council of the Welsh National Branch of the People's League of Health: Professor Edgar Collis, Preventative Medicine, Chair South Wales University; Colonel Lyle Cummins, Tuberculosis, Chair South Wales University; Mr. Ewen J. Maclean, South Wales University; E.W. Evans, Esq., President of the King Edward VII. Welsh Memorial. A letter signed by members of this council was sent to the Prime Minister, The Right Hon. David Lloyd George, O.M., begging his acceptance of the Presidency of the Welsh National Branch. He has been pleased to honour us by granting our request. Liaison Committee with the Ministry of Health. A Liaison Committee was created between the Ministry of Health and the People's League of Health in June, 1921, consisting of the following official members of the League :— SIR BRUCE BRUCE-PORTER, K.B.E., C.M.G., M.P. SIR ALFRED FRIPP, K.C.V.O., C.B., M.S., F.R.C.S. SIR HARRY BALDWIN, L.D.S., M.R.C.S. DR. BUTTAR. MISS OLGA NETHERSOLE, R.R.C. Through this Committee, the League is able to obtain from the Ministry help and information regarding statistics and other matters for its Health Propaganda work, and has access to the Ministry at any time, through its Chief Medical Officer, Sir George Newman, K.C.B., M.D., F.R.S.D., D.P.H., F.R.C.P., and is privileged to lay before him matters affecting the health of the people which have come to the knowledge of the League and which directly concern the Ministry, who alone have the power to take remedial action. Juvenile Courts and Medical Examination of all Children brought before the Magistrate In October, 1920, the attention of the Medical Council of the League was drawn by Mr. W. Clarke Hall, magistrate of Old Street Police Court, and member of the Lay Council of the League, to the need of a more careful physiological and psychological study being made of all juveniles charged with criminal offences, at the same time pointing out that all students of penology were convinced of the important bearing which mental and physical disabilities have upon criminal tendencies. These predisposing causes, in his opinion, had never been sufficiently studied and recognised in this country, and he pleaded the support of the League for a more enlightened policy governing juveniles and adults charged with criminal offences, and urged that they should be medically examined before being brought into the Courts. The Medical Council expressed itself as being in entire sympathy with Mr. Clarke Hall, and promised its warmest support in any action which he should deem advisable to take. Subsequently the attention of the Home Office was directed to this matter, and many lectures upon the subject have been arranged by the League and delivered by Dr. W.A. Potts, M.A., M.D., under the title of "Crime and Delinquency in their relation to Heredity, Environment and Disease." 33 200/B/3/2/C693/1/71